2015
DOI: 10.1007/s00221-015-4252-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute arm crank ergometry and cycle ergometry on postural sway and attentional demands during quiet bipedal standing

Abstract: Current evidence suggests that acute bouts of lower limb exercise elicits a number of adverse effects on both sensory and motor components of postural control. The effects of acute exercise on quiet standing balance while concurrently performing an attentional task remains equivocal. This study aimed to compare the alterations in postural control and attentional demands elicited by upper and lower limb exercise. Twelve healthy young males (mean ± SD age, 22.2 ± 3.2 years) were examined on six separate occasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…The current study found significant M-L variability following upper body fatigue; however, previous studies investigating postural sway following upper body fatigue identified no significant differences in M-L variability [9][10][11]. The findings of the study supported previous research in that A-P variability and path length showed no significant difference following upper-body fatigue [9][10][11].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The current study found significant M-L variability following upper body fatigue; however, previous studies investigating postural sway following upper body fatigue identified no significant differences in M-L variability [9][10][11]. The findings of the study supported previous research in that A-P variability and path length showed no significant difference following upper-body fatigue [9][10][11].…”
Section: Discussionsupporting
confidence: 69%
“…Previous research has found that upper-body fatigue produced no significant balance impairments [9][10][11]. However, this previous literature has only employed the arm crank ergometer as the mode of exercise to attain upper body fatigue [9][10][11].…”
Section: The Effects Of Upper -Body and Lower -Body Fatigue On Standimentioning
confidence: 95%